The Effect of Gossiping Group Activities Toward Fluency in Speaking at the 10th Grade Of MAN 3 Agam - Alfina, Alfina; Eliza, Eliza; Roza, Veni; Melani, Melyann (Education Achievement: Journal of Science and Research, 2024)
This research was motivated by the findings of the researcher during observations and interviews at the 10th grade of MAN 3 Agam. Researcher found that students often used pause fillers such as "hmm" and "eee", and had low vocabulary mastery that hindered fluency in speaking. They also had difficulty expressing ideas and opinions, so the speed and tempo of speaking were affected. The study aimed to determine the effect of gossiping group activities on students' speaking fluency. The study used a type of experimental research, namely a quasi-experiment with a nonequivalent control group design. The sample in this study was selected using a random technique and the selected class was XE.2 class as the control class and XE.4 class as the experimental class. Instruments in the form of oral speaking tests that had been validated with content validity and assessed with inter-rater reliability. Data analysis included prerequisite tests for normality and homogeneity, and utilized Paired sample t-Tests and Independent sample t-Tests to test hypotheses. From the results of data analysis, it was concluded that gossiping group activities had a significant effect on improving students' speaking fluency.